Factors that contribute to the organization performance in Bank Kerjasama Rakyat Malaysia Berhad / Nik Nurul Idayu Nik Yahya - Nik Yahya, Nik Nurul Idayu (Faculty of Business and Management, 2010)
The main purpose the establishment of bank is to provide a safety place to safe deposits by customer. It provides more security and customer will gaining more benefit with bank relationship. In this study, the focuses on factors that contribute to the Bank Kerjasama Rakyat Malaysia Berhad with the selected variables were examined. The sample banks that choose are Bank Kerjasama Rakyat Malaysia Berhad headquarters and selected branches. This paper presents an alternative perspective on the relationship of organization performance and knowledge acquisition, knowledge sharing, learning environment, meeting learning and development needs and applying learning at the workplace. The dependent variable is organization performance and independent variables would be knowledge acquisition, knowledge sharing, learning environment, identifying learning and development needs, meeting learning and development needs and applying learning at the workplace. By using SPSS software (version 16.0), Multiple Regression, Regression Coefficient, Coefficient of Determination (R2), Alpha Cronbach’s, and Pearson Correlation were analysed and interpreted from data collected. By using Analyse and choose Scale for Reliability tested, knowledge acquisition, knowledge sharing, learning environment and applying learning at the workplace are significant for Bank Rakyat Kerjasama Malaysia Berhad. Meeting learning and development needs have acceptable result.